The spaces of religion: a view from South Asia - Gellner, DN (Wiley, 2023)
Anthropologists have spilt much ink deconstructing concepts inherited from the Enlightenment. Religion, possibly the most misleading such concept, has proved highly resistant to the acid of cross-cultural comparison. Debates about the nature of religion go back to sociocultural anthropology’s beginnings as a discipline and beyond. Proposed definitions have been numerous, but none has come close to universal acceptance, mainly because conventional definitions derive from secularized versions of Abrahamic, and especially Protestant, essentialism and intellectualism. I argue that by looking closely at the way religious phenomena are conceptualized in South Asia, and especially at how distinct types of religion are practised in characteristically different spaces, a fresh take on the subject is possible. Religion as practised is not one thing but (at least) three distinct activities and should be conceptualized as such. But, if that is so, how and why is the totalizing conventional view still so pervasive and so powerful? Seeking the answer to that question takes us back to the constitution of modernity and the relationship of religion to the nation-state. The way forward is to contest the way in which religion has become the last bastion of pure essentialism.